Micromagnetic simulation study of a disordered model for one-dimensional granular perovskite manganite oxide nanostructures - Longone, Pablo Jesus (2018)
Chemical techniques are an efficient method to synthesize one-dimensional perovskite manganite oxide nanostructures with a granular morphology, that is, formed by arrays of monodomain magnetic nanoparticles. Integrating the stochastic Landau-Lifshitz-Gilbert equation, we simulate the dynamics of a simple disordered model for such materials that only takes into account the morphological characteristics of their nanograins. We show that it is possible to describe reasonably well experimental hysteresis loops reported in the literature for single La0.67Ca0.33MnO3 nanotubes and powders of these nanostructures, simulating small systems consisting of only 100 nanoparticles.